The Influence Of Customer Value, Customer Trust And Electronic Service Quality On Customer Satisfaction Of Traveloka - Yusi Faizathul Octavia; Luh Komang Candra Dewi; Donny Dharmawan; Silvia Ekasari; Hery Erdi (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2024)
The purpose of this study is to determine whether customer value, trust, and e-service quality affect customer satisfaction. In this research, the population is active internet users who are familiar with online transactions, the number of which is unknown or can be said to be in the infinite category. This study's sample strategy combines a purposive sampling approach with a non-probability sampling technique. There were 100 samples used in this investigation. Both primary and secondary data are used in this study. Researchers employed web-based electronic questionnaires and online research tools to obtain primary data. Numerous inferences can be made based on the study's findings and the subsequent discussion, including the following: Customer satisfaction is significantly improved by the quality of e-services. Customer satisfaction is significantly positively impacted by customer value. Customer pleasure is positively impacted by trust. Customer happiness is influenced simultaneously by e-service quality, customer value, and trust.